Sinfully sexy a novel - Lee, Linda Francis (New York Random House Publication, 2004)
"Plain-Jane Chloe Sinclair has never been bad... until she stumbles- literally- into the arms of a gorgeous stranger. To make matters worse, her world is rocked completely off its axis the morning after when the sensual dreamboat turns out to be the man brought in to save the TV station where she works."--Back Cover.
"An Ivy Book."
UCWS-3279g donated by Delia Co
Keywords: Women television producers and directors -- Texas -- Fiction; Television programs -- Planning -- Fiction; Television programs -- Production and direction -- Fiction; Sex in the workplace -- Fiction; Love stories